2018
DOI: 10.1590/1809-6891v19e-49000
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Electrocardiographic Study of Dogs at the Veterinary Hospital of Pontifícia Universidade Católica Do Paraná

Abstract: Electrocardiogram is considered a substantial instrument in the clinical evaluation of patients with heart disease. This tool can be used to determine the origin and frequency of the impulse as well as the cardiac conduction disorders. The aim of this study was to evaluate the frequency and type of electrocardiographic abnormalities in the immediate preoperative period of 60 dogs seen in the surgery department of the Veterinary Hospital of Pontifícia Universidade Católica do Paraná -PUCPR, campus Toledo, betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…In addition, conduction disorders are relatively common in dogs, even those without heart disease, due to the physiological predominance of parasympathetic over sympathetic tone, predisposing dogs to the appearance of bradyarrhythmias, such as the atrioventricular block (AVB) diagnosed in the study ( Van Vliet et al 1995). These findings corroborate the findings of previous studies that demonstrated the prevalence of these disorders in a large number of animals (Patterson et al 1961), but more recent studies carried out by Carvalho et al (2009) and Silveira et al (2018) showed a lower frequency of these arrhythmias, which may be related to the absence of symptoms. Although first-and second-degree AVBs can be asymptomatic and therefore of no clinical importance, Risk of arrhythmias in dogs with structural heart disease Santilli et al (2016) demonstrated the progression of AVB degrees in 21.8% of the animals evaluated, and these findings are clinically relevant.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, conduction disorders are relatively common in dogs, even those without heart disease, due to the physiological predominance of parasympathetic over sympathetic tone, predisposing dogs to the appearance of bradyarrhythmias, such as the atrioventricular block (AVB) diagnosed in the study ( Van Vliet et al 1995). These findings corroborate the findings of previous studies that demonstrated the prevalence of these disorders in a large number of animals (Patterson et al 1961), but more recent studies carried out by Carvalho et al (2009) and Silveira et al (2018) showed a lower frequency of these arrhythmias, which may be related to the absence of symptoms. Although first-and second-degree AVBs can be asymptomatic and therefore of no clinical importance, Risk of arrhythmias in dogs with structural heart disease Santilli et al (2016) demonstrated the progression of AVB degrees in 21.8% of the animals evaluated, and these findings are clinically relevant.…”
Section: Discussionsupporting
confidence: 87%
“…Electrocardiography, a non-invasive diagnostic tool, is extensively utilized in veterinary practice for its utility in diagnosing cardiac conditions. Nevertheless, factors such as the use of different devices can introduce variability in electrocardiographic tracings, potentially affecting interpretation accuracy (Figueiredo et al, 2016;Ferreira et al, 2017;Silveira et al, 2018;Porsani et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Electrocardiography serves as a crucial diagnostic method that charts the electrical potentials produced by the heart, showcasing myocardial depolarization and repolarization phases (Porsani et al, 2020). By virtue of its properties, this technique is capable of identifying alterations in electrical impulse flow, impulse origins, and their frequencies (Silveira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation